Water characteristic curve of soil with bimodal grain-size distribution - Satyanaga, Alfrendo (2013)
Soil–water characteristic curve (SWCC) is the most fundamental and important soil property in unsaturated soil mechanics. It has been used for analyzing slope stability due to the infiltration of rainfall into slopes and water flow in unsaturated embankments. Generally, SWCC is obtained by laboratory tests. However high cost, long duration and difficulty of the tests impede the application of unsaturated soil mechanics to practical design or analysis. Therefore, several equations have been developed to predict the SWCC using grain-size distribution (GSD) curve. However, most of the equations were limited to soils with unimodal characteristics and the parameters of the equations are not related to the physical properties of the soil. In this paper, an equation to predict SWCC for soils with bimodal characteristics is proposed. The parameters of the proposed equation are related to the physical properties of soil and the variables of SWCC closely. The proposed equation is evaluated with data from the literature and laboratory tests carried out in this study. In addition, the computer codes for the computation of the predicted bimodal SWCC are presented.